Attribute theorems as a prtotypic type of relative clauses in contemporary German: A theoretical study - MAHMOD, UDAY HATTIM (Al-Adab Journal, 2021)
In this project, we try to do justice to the grammatical phenomenon of the current German language, which we want to explain in this research. This study deals with the topic of attribute theorems as a prtotypic type of relative clauses in contemporary German, not only from the grammatical or syntactic level, but also from the semantic level. The presented work thus covers the most important rules of the relative clause as an attribute with regard to: a) Construction and formation of the attribute theorem as a prototypical type of relative clauses in German. b) Meaning and use of attribute theorem as a prototypical type of relative clauses in German.